Swimming Activity of Gilthead Seabream (Sparus aurata) in Swim-Tunnels: Accelerations, Oxygen Consumption and Body Motion - Arechavala-Lopez, Pablo; Lankheet, Martin J.; Díaz-Gil, Carlos; Abbink, Wout; Palstra, Arjan P. (Frontiers in Animal Science, 2021)
Acoustic accelerometry is considered a useful tool to study swimming activity, including energetics and movement patterns, of fish species in aquaculture and in nature. However, given the novelty of this technique, further laboratory-derived calibrations are needed to assess the characteristics and settings of transmitters for different species and specific environmental conditions. In this study, we compared acoustic accelerometer outputs with swimming performance and body motion of gilthead seabream (Sparus aurata L.) in swim-tunnels at different flow speeds, which allowed us to characterize the swimming activity of this fish species of high aquaculture interest. Tag implantation in the abdominal cavity had no significant effects on swimming performance and body motion parameters. Accelerations, cost of transport and variations on head orientation (angle with respect to flow direction) were negatively related to flow speed in the tunnel, whereas oxygen consumption and frequencies of tail-beat and head movements increased with flow speed. These results show that acoustic accelerometer mainly recorded deviations from sustained swimming in the tunnel, due to spontaneous and explorative swimming at the lowest speeds or intermittent burst and coast actions to cope with water flow. In conclusion, acoustic accelerometers provides a proxy for unsustained swimming activity, but did not contemplate the high-energy cost spent by gilthead seabream on sustained swimming, and therefore, it did not provide a proxy for general activity. Despite this limitation, accelerometers provide valuable insight in swim patterns and therefore may be a good strategy for advancing our understanding of fish swimming behaviour in aquaculture, allowing for rapid detection of changes in species-specific behavioural patterns considered indicators of fish welfare status, and assisting in the refinement of best management practices.